IPad mini for dummies - Baig, Edward C.; LeVitus, Bob (--For dummies., 2015)
Big info about using the iPad mini! This fun-and-friendly full-color book gets you started with your iPad mini, walking you through using the multitouch interface, getting connected, going online, and packing your iPad mini with apps, games, e-books, photos, music, movies, and more. Expert authors and Mac gurus Edward C. Baig and Bob "Dr. Mac" LeVitus guide you through everything from powering up all the way to syncing your stuff with iCloud. You'll learn how to manage your calendar, make video calls with FaceTime, work with Siri, and enjoy your iPad mini wherever you go